Preparation process of wear-resistant quartz sand ceramic material

By pretreating quartz sand and combining with iron oxide modified kaolin and other materials, quartz sand ceramic materials with excellent mechanical properties, wear resistance and high temperature stability are prepared, which solves the shortcomings of traditional quartz ceramic materials in wear resistance, high temperature stability and weather resistance.

CN119841618AActive Publication Date: 2025-04-18YUNFU CITY YUNAN DISTRICT SONGXIN BUILDING CERAMICS RAW MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510066567.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-18
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

Traditional quartz ceramic materials have shortcomings in wear resistance, high temperature stability and weather resistance, and are difficult to meet the high requirements in certain specific fields.

Method used

By pretreating quartz sand, combined with mixing and sintering of iron oxide modified kaolin, barium carbonate, titanium diboride, aluminum nitride, alumina and titanium dioxide, quartz sand ceramic materials with excellent mechanical properties, wear resistance and high temperature cycle stability were prepared.

Benefits of technology

It significantly improves the hardness and wear resistance of ceramic materials, enhances its stability at high temperatures, and improves the overall performance and service life of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005244506190000121
    Figure BDA0005244506190000121
  • Figure BDA0005244506190000131
    Figure BDA0005244506190000131
Patent Text Reader

Abstract

The invention provides a preparation process of a wear-resistant quartz sand ceramic material, and relates to the technical field of ceramic materials. The preparation process comprises the following steps: pretreating quartz sand, uniformly mixing the pretreated quartz sand with iron oxide modified kaolin, barium carbonate, titanium diboride, aluminum nitride, aluminum oxide and titanium dioxide to obtain a base material, adding an additive accounting for 3-7% of the weight of the base material, and stirring and dispersing to obtain mixed powder; filling the mixed powder into a mold, pressing to obtain a ceramic blank, sintering, and naturally cooling to room temperature to obtain the ceramic. By optimizing the raw material ratio, improving the preparation process and adding the specific additive, the prepared quartz sand ceramic material has excellent mechanical properties, wear resistance and high-temperature cycle stability, and provides powerful technical support for development of related fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wear-resistant materials, and in particular to a preparation process of a wear-resistant quartz sand ceramic material. Background Art

[0002] As a silicate raw material, quartz sand is widely used in ceramics, glass, casting, construction, chemicals, abrasives and other fields due to its high hardness, wear resistance and stable chemical properties. However, natural quartz sand often contains various impurities and needs to be purified through specific processes to meet the demand for high-quality products. In the preparation of ceramic materials, the purity and particle size of quartz sand have a crucial impact on the performance of the final product.

[0003] When preparing wear-resistant quartz sand ceramic materials, in addition to requiring high purity of raw materials, attention should also be paid to its wear resistance, stability at different temperatures and weather resistance. Traditional quartz ceramic materials have deficiencies in wear resistance, high temperature stability and weather resistance, and it is difficult to meet the high requirements of certain specific fields. Based on this, the present invention provides a preparation process of wear-resistant quartz sand ceramic materials. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation process of a wear-resistant quartz sand ceramic material. The prepared quartz sand ceramic material has excellent mechanical properties, wear resistance and high-temperature cycle stability.

[0005] On the one hand, the present invention provides a preparation process of wear-resistant quartz sand ceramic material, comprising the following steps: pre-treating quartz sand and uniformly mixing it with iron oxide-modified kaolin, barium carbonate, titanium diboride, aluminum nitride, aluminum oxide and titanium dioxide to obtain a base material, adding 3-7% of an additive relative to the weight of the base material, stirring and dispersing the additive to obtain a mixed powder, charging the mixed powder into a mold and pressing the mold to obtain a ceramic body, and then naturally cooling the mold to room temperature after sintering.

[0006] Furthermore, the quartz sand pretreatment step includes: immersing the quartz sand in a 20-30% HCl aqueous solution for 24-26 hours, washing with deionized water until neutral, drying and grinding at 60-80° C., and finally passing through a 100-200 mesh sieve.

[0007] Furthermore, the preparation method of the iron oxide modified kaolin includes: calcining kaolin with a particle size of 70-80 μm at 800-840° C. for 2-3 hours, cooling to room temperature, mixing with cocamidopropyl betaine and ethanol, adding iron oxide at a temperature of 60-80° C. and a stirring speed of 140-160 rpm, continuing to stir for 120-140 minutes, drying at 100-110° C. to constant weight, and grinding to obtain the product.

[0008] Furthermore, the weight ratio of kaolin, cocamidopropyl betaine, ethanol and iron oxide is (1-2): (0.2-0.3): (2-3): (0.5-1).

[0009] Furthermore, the base material includes the following materials in parts by weight: 8-12 parts of pretreated quartz sand, 10-12 parts of iron oxide modified kaolin, 4-6 parts of barium carbonate, 2-4 parts of titanium diboride, 3-5 parts of aluminum nitride, 4-6 parts of aluminum oxide, and 6-10 parts of titanium dioxide.

[0010] Furthermore, the additives include a binder, a plasticizer, a lubricant and a dispersant in a weight ratio of (20-50): (5-10): (1-5): (6-30).

[0011] Furthermore, the binder is polyvinyl alcohol, the plasticizer is emulsified paraffin, and the lubricant is oleic acid.

[0012] Furthermore, the dispersant includes sodium dodecylbenzene sulfonate and polyacrylate in a weight ratio of 1:5.

[0013] Furthermore, the pressure during pressing is 60-80 MPa.

[0014] Furthermore, the sintering step includes: firing at 200-300°C for 4-6 hours, heating to 700-800°C at a heating rate of 3-5°C / min, keeping warm for 2-4 hours, then heating to 1100-1200°C at a heating rate of 3-5°C / min, and keeping warm for 2-4 hours.

[0015] The beneficial effects of the present invention are:

[0016] The present invention pre-treats the quartz sand by immersing it in an HCl aqueous solution, which can effectively remove impurities and attachments on the surface of the quartz sand, and at the same time slightly etch its surface to increase its bonding strength with other components. The quartz sand particles after drying and grinding are evenly distributed, which helps to improve the overall density and strength of the ceramic material;

[0017] The addition of hard phase components such as titanium diboride and aluminum nitride in the present invention significantly improves the hardness and wear resistance of the ceramic material. These hard phases play a "skeleton" role in the ceramic material and can resist external wear and scratches. The addition of components such as aluminum oxide and titanium dioxide enhances the stability of the ceramic material at high temperatures. These components have a high melting point and good thermal stability and can maintain stable performance in a high temperature environment.

[0018] The present invention adopts kaolin modified by iron oxide as the main raw material. After high-temperature calcination, the crystal water in the kaolin is removed, and the crystal structure is changed, thereby becoming more stable. The calcination process also changes the surface properties of the kaolin, making it easier to combine with iron oxide; the calcined kaolin is mixed with cocamidopropyl betaine and ethanol to form a high-quality dispersion system. The addition of iron oxide not only improves the performance of kaolin, but also enhances the hardness and wear resistance of the ceramic material; cocamidopropyl betaine, as a surfactant, promotes the uniform mixing of the components, and further improves the overall performance of the ceramic material.

[0019] Iron oxide itself has excellent wear resistance. Its introduction significantly improves the wear resistance of quartz sand ceramic materials. The uniform distribution of iron oxide-modified kaolin in ceramic materials helps reduce wear points and extend the service life of the material. In addition, iron oxide and kaolin can form a chemical bond to produce a stable chemical bond. This combination further enhances the structural stability of kaolin, making it less likely to decompose or undergo phase change in high-temperature environments. The distribution of iron oxide particles on the surface or between layers of kaolin forms a thermal barrier that slows down the transfer of heat to the interior of kaolin. This helps reduce the thermal stress of kaolin at high temperatures, thereby reducing the possibility of structural damage.

[0020] The additives used in the present invention include a binder, a plasticizer, a lubricant and a dispersant, wherein the binder polyvinyl alcohol can enhance the cohesion of the ceramic material and make it stronger; the plasticizer emulsified paraffin can improve the plasticity of the ceramic material and make it easier to shape; the lubricant oleic acid can reduce the friction resistance of the ceramic material during the pressing process and improve the pressing efficiency; the dispersant such as sodium dodecylbenzene sulfonate and polyacrylate can ensure that various raw materials are evenly dispersed during the mixing process to avoid the occurrence of agglomeration.

[0021] In the present invention, sodium dodecylbenzene sulfonate and polyvinyl ester are selected as dispersants, wherein sodium dodecylbenzene sulfonate can be adsorbed on the surface of quartz sand particles in the preparation process of quartz sand ceramic material to form a layer of wetting film, which can prevent the reunion between particles and make the quartz sand particles uniformly dispersed in water, thereby improving the uniformity and compactness of the material. And the molecular structure of sodium dodecylbenzene sulfonate enables it to form chemical bonding or physical adsorption with the inorganic components in the ceramic material, and this combination can enhance the interfacial bonding force between the quartz sand particles and the ceramic matrix, thereby improving the mechanical properties of the material. And the addition of polyvinyl ester can increase the toughness of the material, so that it can better absorb and disperse energy when subjected to external force, thereby reducing the wear and peeling of the material surface, and improving wear resistance. On this basis, the compounding of sodium dodecylbenzene sulfonate and polyvinyl ester can produce a synergistic effect, each plays an advantage, and complements each other. This composite dispersant can more effectively reduce the reunion phenomenon between the quartz sand particles, and improve the uniformity and compactness of the material. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] It should be noted that the model of the polyvinyl alcohol in the present invention is PVA-1788, the model of the emulsified paraffin is E-200, and the model of the polyvinyl ester is EEA A713.

[0024] Example 1

[0025] This embodiment provides a preparation process of a wear-resistant quartz sand ceramic material, the steps comprising:

[0026] The pretreatment steps of the quartz sand include: immersing the quartz sand in a 25% HCl aqueous solution for 25 hours, washing with deionized water until neutral, drying and grinding at 70° C., and finally passing through a 150-mesh sieve;

[0027] The preparation method of iron oxide modified kaolin includes: calcining kaolin with a particle size of 75 μm at 820° C. for 2.5 hours, cooling to room temperature, mixing with cocamidopropyl betaine and ethanol, adding iron oxide at a temperature of 70° C. and a stirring speed of 150 rpm, continuing to stir for 130 minutes, drying at 105° C. to constant weight, and grinding to obtain the obtained product; the weight ratio of the kaolin, cocamidopropyl betaine, ethanol and iron oxide is 0.5:0.25:2.5:0.7;

[0028] Preparation of wear-resistant quartz sand ceramic material: According to weight parts, 10 parts of pretreated quartz sand, 11 parts of iron oxide modified kaolin, 5 parts of barium carbonate, 3 parts of titanium diboride, 4 parts of aluminum nitride, 5 parts of aluminum oxide, and 8 parts of titanium dioxide are mixed evenly to obtain a base material, and 5% of additives relative to the weight of the base material are added and stirred and dispersed to obtain a mixed powder. After the mixed powder is loaded into a mold, it is pressed at a pressure of 70 MPa to obtain a ceramic body, fired at 250°C for 5h, heated to 750°C at a heating rate of 4°C / min, and kept warm for 3h, and then heated to 1150°C at a heating rate of 4°C / min, and kept warm for 3h. After sintering, it is naturally cooled to room temperature.

[0029] Among them, the additives include a binder, a plasticizer, a lubricant and a dispersant in a weight ratio of 35:7.5:3:18; the binder is polyvinyl alcohol, the plasticizer is emulsified paraffin, and the lubricant is oleic acid; the dispersant includes sodium dodecylbenzene sulfonate and polyvinyl ester in a weight ratio of 1:5.

[0030] Example 2

[0031] This embodiment provides a preparation process of a wear-resistant quartz sand ceramic material, the steps comprising:

[0032] The pretreatment steps of the quartz sand include: immersing the quartz sand in a 20% HCl aqueous solution for 26 hours, washing with deionized water until neutral, drying and grinding at 80° C., and finally passing through a 100-mesh sieve;

[0033] The preparation method of iron oxide modified kaolin includes: calcining kaolin with a particle size of 70 μm at 820° C. for 2 hours, cooling to room temperature, mixing with cocamidopropyl betaine and ethanol, adding iron oxide at a temperature of 80° C. and a stirring speed of 140 rpm, continuing to stir for 140 minutes, drying at 100° C. to constant weight, and grinding to obtain the obtained product; the weight ratio of the kaolin, cocamidopropyl betaine, ethanol and iron oxide is 1:0.2:2:0.5;

[0034] Preparation of wear-resistant quartz sand ceramic material: 9 parts of pretreated quartz sand, 10 parts of iron oxide modified kaolin, 5 parts of barium carbonate, 2 parts of titanium diboride, 3 parts of aluminum nitride, 4 parts of aluminum oxide, and 7 parts of titanium dioxide are mixed evenly according to weight to obtain a base material, and 4% of additives relative to the weight of the base material are added and stirred and dispersed to obtain a mixed powder. After the mixed powder is loaded into a mold, it is pressed at a pressure of 65 MPa to obtain a ceramic body, fired at 240°C for 4h, heated to 700°C at a heating rate of 5°C / min, kept warm for 2h, and then heated to 1100°C at a heating rate of 5°C / min, kept warm for 4h, and naturally cooled to room temperature after sintering.

[0035] Among them, the additives include a binder, a plasticizer, a lubricant and a dispersant in a weight ratio of 30:6:3:15; the binder is polyvinyl alcohol, the plasticizer is emulsified paraffin, and the lubricant is oleic acid; the dispersant includes sodium dodecylbenzene sulfonate and polyvinyl ester in a weight ratio of 1:5.

[0036] Example 3

[0037] This embodiment provides a preparation process of a wear-resistant quartz sand ceramic material, the steps comprising:

[0038] The pretreatment steps of the quartz sand include: immersing the quartz sand in a 30% HCl aqueous solution for 24 hours, washing with deionized water until neutral, drying and grinding at 80° C., and finally passing through a 100-mesh sieve;

[0039] The preparation method of iron oxide modified kaolin includes: calcining kaolin with a particle size of 80 μm at 840° C. for 2 hours, cooling to room temperature, mixing with cocamidopropyl betaine and ethanol, adding iron oxide at a temperature of 70° C. and a stirring speed of 140 rpm, continuing to stir for 140 minutes, drying at 100° C. to constant weight, and grinding to obtain the obtained product; the weight ratio of the kaolin, cocamidopropyl betaine, ethanol and iron oxide is 2:0.3:3:0.6;

[0040] Preparation of wear-resistant quartz sand ceramic material: 11 parts of pretreated quartz sand, 10 parts of iron oxide modified kaolin, 6 parts of barium carbonate, 4 parts of titanium diboride, 3 parts of aluminum nitride, 6 parts of aluminum oxide, and 8 parts of titanium dioxide are mixed evenly according to weight to obtain a base material, and 6% of additives relative to the weight of the base material are added and stirred and dispersed to obtain a mixed powder. After the mixed powder is loaded into a mold, it is pressed at a pressure of 80 MPa to obtain a ceramic body, which is fired at 300°C for 4h, heated to 700°C at a heating rate of 3°C / min, kept warm for 2h, and then heated to 1200°C at a heating rate of 3°C / min, kept warm for 2h, and naturally cooled to room temperature after sintering.

[0041] Among them, the additives include a binder, a plasticizer, a lubricant and a dispersant in a weight ratio of 40:8:4:20; the binder is polyvinyl alcohol, the plasticizer is emulsified paraffin, and the lubricant is oleic acid; the dispersant includes sodium dodecylbenzene sulfonate and polyvinyl ester in a weight ratio of 1:5.

[0042] Example 4

[0043] This embodiment provides a preparation process of a wear-resistant quartz sand ceramic material, the steps comprising:

[0044] The pretreatment steps of the quartz sand include: immersing the quartz sand in a 25% HCl aqueous solution for 26 hours, washing with deionized water until neutral, drying and grinding at 80° C., and finally passing through a 200-mesh sieve;

[0045] The preparation method of iron oxide modified kaolin includes: calcining kaolin with a particle size of 80 μm at 840° C. for 2 hours, cooling to room temperature, mixing with cocamidopropyl betaine and ethanol, adding iron oxide at a temperature of 80° C. and a stirring speed of 140 rpm, continuing to stir for 140 minutes, drying at 100° C. to constant weight, and grinding to obtain the obtained product; the weight ratio of the kaolin, cocamidopropyl betaine, ethanol and iron oxide is 1.5:0.2:2:1;

[0046] Preparation of wear-resistant quartz sand ceramic material: 10 parts of pretreated quartz sand, 11 parts of iron oxide modified kaolin, 6 parts of barium carbonate, 4 parts of titanium diboride, 5 parts of aluminum nitride, 4 parts of aluminum oxide, and 6 parts of titanium dioxide are mixed evenly according to weight to obtain a base material, and 5% of additives relative to the weight of the base material are added and stirred and dispersed to obtain a mixed powder. After the mixed powder is loaded into a mold, it is pressed at a pressure of 80 MPa to obtain a ceramic body, fired at 300°C for 4h, heated to 700°C at a heating rate of 5°C / min, kept warm and fired for 4h, and then heated to 1100°C at a heating rate of 3°C / min, kept warm and fired for 4h, and naturally cooled to room temperature after sintering.

[0047] Among them, the additives include a binder, a plasticizer, a lubricant and a dispersant in a weight ratio of 25:7:4:16; the binder is polyvinyl alcohol, the plasticizer is emulsified paraffin, and the lubricant is oleic acid; the dispersant includes sodium dodecylbenzene sulfonate and polyvinyl ester in a weight ratio of 1:5.

[0048] Comparative Example 1

[0049] This comparative example provides a preparation process of a wear-resistant quartz sand ceramic material, the steps comprising:

[0050] The pretreatment steps of the quartz sand include: immersing the quartz sand in a 25% HCl aqueous solution for 25 hours, washing with deionized water until neutral, drying and grinding at 70° C., and finally passing through a 150-mesh sieve;

[0051] The preparation method of iron oxide modified kaolin comprises: calcining kaolin with a particle size of 75 μm at 820° C. for 2.5 hours, cooling to room temperature, mixing with silane coupling agent KH560 and ethanol, adding iron oxide at a temperature of 70° C. and a stirring speed of 150 rpm, continuing to stir for 130 minutes, drying at 1050° C. to constant weight, and grinding to obtain the obtained product; the weight ratio of kaolin, silane coupling agent KH560, ethanol and iron oxide is 0.5:0.25:2.5:0.7;

[0052] Preparation of wear-resistant quartz sand ceramic material: 10 parts of pretreated quartz sand, 11 parts of iron oxide modified kaolin, 5 parts of barium carbonate, 3 parts of titanium diboride, 4 parts of aluminum nitride, 5 parts of aluminum oxide, and 8 parts of titanium dioxide are mixed evenly according to weight to obtain a base material, and 5% of additives relative to the weight of the base material are added and stirred and dispersed to obtain a mixed powder. After the mixed powder is loaded into a mold, it is pressed at a pressure of 70 MPa to obtain a ceramic body, fired at 250°C for 5h, heated to 750°C at a heating rate of 4°C / min, and kept warm for 3h, and then heated to 1150°C at a heating rate of 4°C / min, and kept warm for 3h. After sintering, it is naturally cooled to room temperature.

[0053] Among them, the additives include a binder, a plasticizer, a lubricant and a dispersant in a weight ratio of 35:7.5:3:18; the binder is polyvinyl alcohol, the plasticizer is emulsified paraffin, and the lubricant is oleic acid; the dispersant includes sodium dodecylbenzene sulfonate and polyvinyl ester in a weight ratio of 1:5.

[0054] Comparative Example 2

[0055] This comparative example provides a preparation process of a wear-resistant quartz sand ceramic material, the steps comprising:

[0056] The pretreatment steps of the quartz sand include: immersing the quartz sand in a 25% HCl aqueous solution for 25 hours, washing with deionized water until neutral, drying and grinding at 70° C., and finally passing through a 150-mesh sieve;

[0057] The preparation method of iron oxide modified bentonite comprises: calcining bentonite with a particle size of 75 μm at 820° C. for 2.5 hours, cooling to room temperature, mixing with cocamidopropyl betaine and ethanol, adding iron oxide at a temperature of 70° C. and a stirring speed of 150 rpm, continuing to stir for 130 minutes, drying at 1050° C. to constant weight, and grinding to obtain the obtained product; the weight ratio of the bentonite, cocamidopropyl betaine, ethanol and iron oxide is 0.5:0.25:2.5:0.7;

[0058] Preparation of wear-resistant quartz sand ceramic material: 10 parts of pretreated quartz sand, 11 parts of iron oxide modified bentonite, 5 parts of barium carbonate, 3 parts of titanium diboride, 4 parts of aluminum nitride, 5 parts of aluminum oxide, and 8 parts of titanium dioxide are mixed evenly according to weight to obtain a base material, and 5% of additives relative to the weight of the base material are added and stirred and dispersed to obtain a mixed powder. The mixed powder is loaded into a mold and pressed at a pressure of 70 MPa to obtain a ceramic body, which is fired at 250°C for 5h, heated to 750°C at a heating rate of 4°C / min, and kept warm for 3h, then heated to 1150°C at a heating rate of 4°C / min, and kept warm for 3h. After sintering, it is naturally cooled to room temperature.

[0059] Among them, the additives include a binder, a plasticizer, a lubricant and a dispersant in a weight ratio of 35:7.5:3:18; the binder is polyvinyl alcohol, the plasticizer is emulsified paraffin, and the lubricant is oleic acid; the dispersant includes sodium dodecylbenzene sulfonate and polyvinyl ester in a weight ratio of 1:5.

[0060] Comparative Example 3

[0061] This comparative example provides a preparation process of a wear-resistant quartz sand ceramic material, the steps comprising:

[0062] The pretreatment steps of the quartz sand include: immersing the quartz sand in a 25% HCl aqueous solution for 25 hours, washing with deionized water until neutral, drying and grinding at 70° C., and finally passing through a 150-mesh sieve;

[0063] The preparation method of iron oxide modified attapulgite comprises: calcining attapulgite with a particle size of 75 μm at 820° C. for 2.5 hours, cooling to room temperature, mixing with cocamidopropyl betaine and ethanol, adding iron oxide at a temperature of 70° C. and a stirring speed of 150 rpm, continuing to stir for 130 minutes, drying at 1050° C. to constant weight, and grinding to obtain the obtained product; the weight ratio of the attapulgite, cocamidopropyl betaine, ethanol and iron oxide is 0.5:0.25:2.5:0.7;

[0064] Preparation of wear-resistant quartz sand ceramic material: 10 parts of pretreated quartz sand, 11 parts of iron oxide modified attapulgite, 5 parts of barium carbonate, 3 parts of titanium diboride, 4 parts of aluminum nitride, 5 parts of aluminum oxide, and 8 parts of titanium dioxide are mixed evenly according to weight to obtain a base material, and 5% of additives relative to the weight of the base material are added and stirred and dispersed to obtain a mixed powder. The mixed powder is loaded into a mold and pressed at a pressure of 70 MPa to obtain a ceramic body, which is fired at 250°C for 5h, heated to 750°C at a heating rate of 4°C / min, and kept warm for 3h, then heated to 1150°C at a heating rate of 4°C / min, and kept warm for 3h. After sintering, it is naturally cooled to room temperature.

[0065] Among them, the additives include a binder, a plasticizer, a lubricant and a dispersant in a weight ratio of 35:7.5:3:18; the binder is polyvinyl alcohol, the plasticizer is emulsified paraffin, and the lubricant is oleic acid; the dispersant includes sodium dodecylbenzene sulfonate and polyvinyl ester in a weight ratio of 1:5.

[0066] Comparative Example 4

[0067] This comparative example provides a preparation process of a wear-resistant quartz sand ceramic material, the steps comprising:

[0068] The pretreatment steps of the quartz sand include: immersing the quartz sand in a 25% HCl aqueous solution for 25 hours, washing with deionized water until neutral, drying and grinding at 70° C., and finally passing through a 150-mesh sieve;

[0069] Preparation of wear-resistant quartz sand ceramic material: 10 parts of pretreated quartz sand, 11 parts of iron oxide and kaolin, 5 parts of barium carbonate, 3 parts of titanium diboride, 4 parts of aluminum nitride, 5 parts of aluminum oxide, and 8 parts of titanium dioxide are mixed evenly according to weight to obtain a base material, and 5% of additives relative to the weight of the base material are added and stirred and dispersed to obtain a mixed powder. The mixed powder is loaded into a mold and pressed at a pressure of 70 MPa to obtain a ceramic body, which is fired at 250°C for 5h, heated to 750°C at a heating rate of 4°C / min, and kept warm for 3h, then heated to 1150°C at a heating rate of 4°C / min, and kept warm for 3h. After sintering, it is naturally cooled to room temperature.

[0070] Among them, the weight ratio of iron oxide and kaolin is 5:7, and the additives include a binder, a plasticizer, a lubricant and a dispersant in a weight ratio of 35:7.5:3:18; the binder is polyvinyl alcohol, the plasticizer is emulsified paraffin, and the lubricant is oleic acid; the dispersant includes sodium dodecylbenzene sulfonate and polyacrylate in a weight ratio of 1:5.

[0071] Comparative Example 5

[0072] This comparative example provides a preparation process of a wear-resistant quartz sand ceramic material, the steps comprising:

[0073] The pretreatment steps of the quartz sand include: immersing the quartz sand in a 25% HCl aqueous solution for 25 hours, washing with deionized water until neutral, drying and grinding at 70° C., and finally passing through a 150-mesh sieve;

[0074] Preparation of wear-resistant quartz sand ceramic material: 10 parts of pretreated quartz sand, 11 parts of kaolin, 5 parts of barium carbonate, 3 parts of titanium diboride, 4 parts of aluminum nitride, 5 parts of aluminum oxide, and 8 parts of titanium dioxide are mixed evenly according to weight to obtain a base material, and 5% of additives relative to the weight of the base material are added and stirred and dispersed to obtain a mixed powder. The mixed powder is loaded into a mold and pressed at a pressure of 70 MPa to obtain a ceramic body, which is fired at 250°C for 5h, heated to 750°C at a heating rate of 4°C / min, and kept warm for 3h, then heated to 1150°C at a heating rate of 4°C / min, and kept warm for 3h. After sintering, it is naturally cooled to room temperature.

[0075] Among them, the additives include a binder, a plasticizer, a lubricant and a dispersant in a weight ratio of 35:7.5:3:18; the binder is polyvinyl alcohol, the plasticizer is emulsified paraffin, and the lubricant is oleic acid; the dispersant includes sodium dodecylbenzene sulfonate and polyvinyl ester in a weight ratio of 1:5.

[0076] Comparative Example 6

[0077] This comparative example provides a preparation process of a wear-resistant quartz sand ceramic material, the steps comprising:

[0078] The pretreatment steps of the quartz sand include: immersing the quartz sand in a 25% HCl aqueous solution for 25 hours, washing with deionized water until neutral, drying and grinding at 70° C., and finally passing through a 150-mesh sieve;

[0079] Preparation of wear-resistant quartz sand ceramic material: 10 parts of pretreated quartz sand, 5 parts of barium carbonate, 3 parts of titanium diboride, 4 parts of aluminum nitride, 5 parts of aluminum oxide, and 8 parts of titanium dioxide are mixed evenly according to weight to obtain a base material, and 5% of additives relative to the weight of the base material are added and stirred and dispersed to obtain a mixed powder. The mixed powder is loaded into a mold and pressed under a pressure of 70 MPa to obtain a ceramic body, which is fired at 250°C for 5h, heated to 750°C at a heating rate of 4°C / min, and kept warm for 3h, then heated to 1150°C at a heating rate of 4°C / min, and kept warm for 3h. After sintering, it is naturally cooled to room temperature.

[0080] Among them, the additives include a binder, a plasticizer, a lubricant and a dispersant in a weight ratio of 35:7.5:3:18; the binder is polyvinyl alcohol, the plasticizer is emulsified paraffin, and the lubricant is oleic acid; the dispersant includes sodium dodecylbenzene sulfonate and polyvinyl ester in a weight ratio of 1:5.

[0081] Test Example: The wear-resistant quartz sand ceramic materials prepared in the above-mentioned Examples 1-4 and Comparative Examples 1-6 were subjected to the following tests.

[0082] 1. Compressive strength: Tested in accordance with GB / T17671-1999 standard;

[0083] 2. Wear resistance: Tested in accordance with GB / T3810.7 standard; wear resistance grades are 1-5, 5 is the best and 1 is the worst, 0: the grinding speed at which wear begins to appear is 100; 1: the grinding speed at which wear begins to appear is 150; 2: the grinding speed at which wear begins to appear is 600; 3: the grinding speed at which wear begins to appear is 755; 4: the grinding speed at which wear begins to appear is 2100; 5: the grinding speed at which wear begins to appear is greater than 12000;

[0084] 3. Thermal stability: Repeatedly raise and lower the temperature of the sample between room temperature and 500°C for 100 times, and then use a metal crack detector to detect cracks. A small number of cracks: the number of cracks per cubic centimeter is 1 to 5, and fine cracks: the number of cracks per cubic centimeter is more than 10.

[0085] The test results are shown in Table 1:

[0086] Table 1: Effect test

[0087]

[0088]

[0089] Finally, it should be noted that the above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents. All technical solutions and improvements that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A process for preparing wear-resistant quartz sand ceramic material, characterized in that the steps include: After pretreatment, quartz sand is mixed with iron oxide-modified kaolin, barium carbonate, titanium diboride, aluminum nitride, aluminum oxide and titanium dioxide to obtain a base material; 3-7% of additives relative to the weight of the base material are added, and mixed powder is obtained after stirring and dispersion; the mixed powder is loaded into a mold and pressed to obtain a ceramic body, and then naturally cooled to room temperature after sintering.

2. The preparation process of a wear-resistant quartz sand ceramic material according to claim 1, characterized in that: The pretreatment steps of quartz sand include: immersing the quartz sand in a 20-30% HCl aqueous solution for 24-26 hours, washing with deionized water until neutral, drying and grinding at 60-80° C., and finally passing through a 100-200 mesh sieve to obtain the quartz sand.

3. The preparation process of a wear-resistant quartz sand ceramic material according to claim 1, characterized in that: The preparation method of the iron oxide modified kaolin comprises: calcining kaolin with a particle size of 70-80 μm at 800-840° C. for 2-3 hours, cooling to room temperature, mixing with cocamidopropyl betaine and ethanol, adding iron oxide at a temperature of 60-80° C. and a stirring speed of 140-160 rpm, continuing to stir for 120-140 minutes, drying at 100-110° C. to constant weight, and grinding to obtain the kaolin.

4. The preparation process of a wear-resistant quartz sand ceramic material according to claim 3, characterized in that: The weight ratio of the kaolin, cocamidopropyl betaine, ethanol and iron oxide is (1-2): (0.2-0.3): (2-3): (0.5-1).

5. The preparation process of a wear-resistant quartz sand ceramic material according to claim 1, characterized in that: The base material comprises the following materials in parts by weight: 8-12 parts of pretreated quartz sand, 10-12 parts of iron oxide modified kaolin, 4-6 parts of barium carbonate, 2-4 parts of titanium diboride, 3-5 parts of aluminum nitride, 4-6 parts of aluminum oxide, and 6-10 parts of titanium dioxide.

6. The preparation process of a wear-resistant quartz sand ceramic material according to claim 5, characterized in that: The additives include a binder, a plasticizer, a lubricant and a dispersant in a weight ratio of (20-50): (5-10): (1-5): (6-30).

7. The preparation process of a wear-resistant quartz sand ceramic material according to claim 6, characterized in that: The binder is polyvinyl alcohol, the plasticizer is emulsified paraffin, and the lubricant is oleic acid.

8. The preparation process of a wear-resistant quartz sand ceramic material according to claim 6, characterized in that: The dispersant includes sodium dodecylbenzene sulfonate and polyacrylate in a weight ratio of 1:

5.

9. The preparation process of a wear-resistant quartz sand ceramic material according to claim 1, characterized in that: The pressure during the pressing is 60-80 MPa.

10. The preparation process of a wear-resistant quartz sand ceramic material according to claim 1, characterized in that: The sintering steps include: firing at 200-300°C for 4-6h, heating to 700-800°C at a heating rate of 3-5°C / min, keeping the temperature for 2-4h, then heating to 1100-1200°C at a heating rate of 3-5°C / min, and keeping the temperature for 2-4h.

Citation Information

Patent Citations

  • Thermal shock resistant thin-walled cordierite honeycomb ceramics and preparation method thereof

    CN102424569A

  • Preparation method of matte iron sand gold ceramic glaze

    CN111423123A

  • Wear-resistant quartz ceramic material and preparation method thereof

    CN112573910A

  • Wear-resistant ceramic tile and preparation method thereof

    CN115745568A

  • High-hardness wear-resistant ceramic tile and preparation method thereof

    CN116354697A